ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PELAKU UKM SEKTOR PERDAGANGAN KIOS DI KECAMATAN ENDE UTARA - Lambertus Langga (ANALISIS, 2021)
This research is the result of research on SMEs in Ende Utara District, Ende Regency with 80 respondents. The research method was carried out with descriptive statistics with the SPSS analysis tool. The results show the first hypothesis, namely that there is a simultaneous influence between the variables of capital sales volume, working hours and location on the income level of kiosk business actors in Ende Utara District, Ende Regency and the second hypothesis states that the initial capital variable has the most dominant influence on the income level of the SMEs Kiosk Actors in Ende Utara District, Ende Regency Keywords: capital, sales volume, working hours and locatin